Roofcake 1 Posted September 24, 2014 So, I'm doing geometry and I felt pretty confident until today when our teacher handed us a worksheet that says 'Write an equation in slope intercept form of a line that passes through the given point and is parallel to the graph of each equation.' So, for example: 2x + y = 5; (3,1) I've got it down to: y = 2x - 5; (3,1) And now I'm stuck. This may seem elementary to some, but I'm not the greatest at math, so any help is appreciated! 0 Share this post Link to post Share on other sites
Guest Vittoria Posted September 24, 2014 This might help? http://www.algebra.com/algebra/homework/Equations.faq.question.21756.html 0 Share this post Link to post Share on other sites
Rick 19 Posted September 24, 2014 Google is your friend with math. I've always been able to find explanations when needed. Youtube can be another good recourse. 0 Share this post Link to post Share on other sites
Roofcake 1 Posted September 24, 2014 This might help? http://www.algebra.com/algebra/homework/Equations.faq.question.21756.html Sorry, already tried it. I believe y = -5, but I have to find the x intercept. 0 Share this post Link to post Share on other sites
Andrew 0 Posted September 24, 2014 This might help? http://www.algebra.com/algebra/homework/Equations.faq.question.21756.html Sorry, already tried it. I believe y = -5, but I have to find the x intercept. 2x + y = 5 Take the 2x over to the other side so it makes it y = -2x + 5 -2 is the gradient (parallel lines have same gradient) y-y1=m(x=x1) y-1= -2(x-3) y=-2x + 7 0 Share this post Link to post Share on other sites
Soren 0 Posted September 24, 2014 the answer is friberg 0 Share this post Link to post Share on other sites
Roofcake 1 Posted September 24, 2014 2x + y = 5 Take the 2x over to the other side so it makes it y = -2x + 5 -2 is the gradient (parallel lines have same gradient) y-y1=m(x=x1) y-1= -2(x-3) y=-2x + 7 How did you get 7? 0 Share this post Link to post Share on other sites
Andrew 0 Posted September 24, 2014 2x + y = 5 Take the 2x over to the other side so it makes it y = -2x + 5 -2 is the gradient (parallel lines have same gradient) y-y1=m(x=x1) y-1= -2(x-3) y=-2x + 7 How did you get 7? y-1 = -2x + 6 then plus the one over. Just expanded the brackets (-2 x -3 = 6) 0 Share this post Link to post Share on other sites
Snoop 0 Posted September 24, 2014 Man, I wish I understood what was going on here. 0 Share this post Link to post Share on other sites